An Aqueous Redox Flow Battery with a Tungsten–Cobalt Heteropolyacid as the Electrolyte for both the Anode and Cathode. Issue 8 (29th December 2016) - Liu, Yiyang; Lu, Shanfu; Wang, Haining; Yang, Chunmei; Su, Xin; Xiang, Yan
Abstract : A tungsten–cobalt heteropolyacid simultaneously acts as the electrolyte in both the positive and negative compartments of an aqueous redox flow battery. The heteropolyacid provides all of the necessary redox pairs and charge carriers for the battery. A high coulombic efficiency of 99% and an energy efficiency of 86% are achieved. Additionally, at a current density of 25 mA cm –2, a specific energy of 15.4 W h L –1 is obtained.